2015
DOI: 10.5194/soil-1-707-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar and liming on soil nitrous oxide emissions from a temperate maize cropping system

Abstract: Abstract. Biochar, a carbon-rich, porous pyrolysis product of organic residues may positively affect plant yield and can, owing to its inherent stability, promote soil carbon sequestration when amended to agricultural soils. Another possible effect of biochar is the reduction in emissions of nitrous oxide (N 2 O). A number of laboratory incubations have shown significantly reduced N 2 O emissions from soil when mixed with biochar. Emission measurements under field conditions however are more scarce and show we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 56 publications
2
29
0
1
Order By: Relevance
“…Furthermore, the calculation of cumulative NO 3 − -derived N 2 O emissions showed that soil biochar amendment significantly decreased N 2 O emissions by 54%. These results confirmed what has been shown in several lab and field studies before11646566676869, that biochar amendment can mitigate soil N 2 O emission. In addition to N 2 O emission reduction, Cayuela and colleagues showed that soil biochar amendment substantially decreased the N 2 O/(N 2 O + N 2 ) emission ratio64.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the calculation of cumulative NO 3 − -derived N 2 O emissions showed that soil biochar amendment significantly decreased N 2 O emissions by 54%. These results confirmed what has been shown in several lab and field studies before11646566676869, that biochar amendment can mitigate soil N 2 O emission. In addition to N 2 O emission reduction, Cayuela and colleagues showed that soil biochar amendment substantially decreased the N 2 O/(N 2 O + N 2 ) emission ratio64.…”
Section: Discussionsupporting
confidence: 90%
“…The field experiment set up by Hüppi et al. () was established on a Eutric Mollic Gleysol ( IUSS Working Group WRB , ) with a clay loam texture (36% clay, 27% silt, 2.6% organic carbon concentration; initial pH = 6.3) at the Agroscope research institute in Zürich, Switzerland (47.4N, 8.5E, 440 m amsl). Mean annual (1981–2010) temperature at the site is 9.4°C and mean annual (1981–2010) precipitation is 1054 mm (data obtained from the Swiss Federal Office of Meteorology and Climatology MeteoSwiss).…”
Section: Methodsmentioning
confidence: 99%
“…The biochar was produced in a Pyreg reactor (Pyreg GmbH, Dörth, Germany) by Verora (Edlibach ZG, Switzerland), using slow pyrolysis and a temperature of approximately 650°C. The biochar had the following properties ( Hüppi et al., ): 64.9% total C, 62.1% organic C, pH 9.8 (1:10 in water), liming capacity 17.2% CaCO 3 , 148 m 2 g −1 BET surface area, and ash content 20%. Element ratios were 0.11 O/C and 0.33 H/C molar, and 94 C/N by mass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms are still not well understood and range from pH effects (e.g. liming; Obia et al 2015;Hüppi et al 2015), to changes in soil N transformations (Nelissen et al 2012), to shifts in the ratio of N 2 O/N 2 end products of denitrification (Cayuela et al 2013). The hypothesis explaining the last mechanism assumes changes in denitrifier gene expression (Harter et al 2014) and nitrate capture .…”
Section: Soil Organic Matter and Greenhouse Gasesmentioning
confidence: 99%